KINERJA BPD (BADAN PERMUSYAWARATAN DESA) DALAM PENYELENGARAAN PEMERINTAHAN DESA DI KECAMATAN LIKUPANG SELATAN - Sasundame, Reinaldi Gisberd; Rumapea, Patar; Rares, Joyce Jacinta (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : This research aims to know the performance of The Village Council Deliberations in the Organization of the Government on the District Southern Likupang. The Village Council Deliberations is a legislative institution of the village stand on behalf of the community. The Village Council Deliberations is an institution which has the task to set the rules of the village, accommodating and channelling the aspirations of the community. But in fact came the gap between reality and expectations, which in the exercise of duty Village Council Deliberations is not maximum The methods used in this research is qualitative, descriptive with the techniques of primary and secondary data collection is done with the interview, observation and documentation study. As for being informants among other things: 1 the head of district,Â  7 the village chief, 7 head of The Village Council Deliberations and 14 people total informants is 29 people in 7 villages in district South Likupang. The research results showed that the performance of The Village Council Deliberations in district South Likupang seen from the implementation of functions which in size with performance measurement indicators (Productivity, Responsiveness, quality of service, corporate responsibility and accountability) is still not optimal. For example in carrying out the task of supervision in all lines is still insufficient, additionally in the hold and disburse the aspirations of society also have yet to pan out. His stuff is so in conducting the election of the members Village Council Deliberations there are often government intervention from the village, it does have an impact on the performance of the membership many inactive in the Organization's work does work. Views of the administrative management are still very bad. So is the case with transparent from The Village Council Deliberations to society that votes haven't been fullest. Referring to the conclusions above, shall recommend in a good cooperation between Government, communities, villages, with The Village Council Deliberations, then County Government shall facilitate the work of The Village Council Deliberations by holding trainings, the main thing in this case is also the awareness and responsibility of each Member of The Village Council Deliberations in their job they are already on the community entrust to them. Keys Words: Performance, The Village Council Deliberations